2022
DOI: 10.1001/jamaoncol.2021.7643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Symptom Monitoring Intervention for Patients Hospitalized With Advanced Cancer

Abstract: IMPORTANCE Symptom monitoring interventions are increasingly becoming the standard of care in oncology, but studies assessing these interventions in the hospital setting are lacking.OBJECTIVE To evaluate the effect of a symptom monitoring intervention on symptom burden and health care use among hospitalized patients with advanced cancer. DESIGN, SETTING, AND PARTICIPANTSThis nonblinded randomized clinical trial conducted from February 12, 2018, to October 30, 2019, assessed 321 hospitalized adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 68 publications
0
36
1
Order By: Relevance
“…K was 0.89 with excellent agreement. Thirteen studies were included, of which nine were quantitative [47][48][49][50][51][52][53][54] (one was a protocol used to evaluate new software [55]), two were qualitative [56,57] and two had a mixed-method design [58,59]. The search and decision-making process is described using the PRISMA flow diagram [43] in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…K was 0.89 with excellent agreement. Thirteen studies were included, of which nine were quantitative [47][48][49][50][51][52][53][54] (one was a protocol used to evaluate new software [55]), two were qualitative [56,57] and two had a mixed-method design [58,59]. The search and decision-making process is described using the PRISMA flow diagram [43] in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…The studies were published from 2011 to 2022 and carried out in several European and non-European countries; the most active country publishing on the topic was the USA [47-49, 54, 58]. In seven studies, the e-PROMS were administered through a touchscreen tablet [48,49,[51][52][53][54]56] and a pen/stylus [51]. Two studies reported the use of smartphones [55,57], and two used computers [58,59].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations